Middlemen of the Cameroons Rivers : the Duala and their Hinterland, c.1600-c.1960. - Austen, Ralph A. (African studies series, 1999)
This is a book about 'middlemen': Africans who functioned as intermediaries between Europeans and their own hinterland for over 300 years. Based on written and oral sources, it follows the Duala, a critical community, from precolonial history to the end of colonialism, covering both German and French colonial role.